Experimental investigation on characteristic change of a scale-extendable chain-type floating structure. (1st October 2020) - Ding, R.; Liu, C.R.; Zhang, H.C.; Xu, D.L.; Shi, Q.J.; Yan, D.L.; Yang, W.Y.; Chen, W.P.; Wu, Y.S.
Abstract: The present paper reports an experimental investigation in order to understand the characteristic evolution of a chain-type floating system with increasing number of modules up to five. Semi-submersible modules are fabricated, connected by hinges and constrained by elastic mooring lines for experimental tests in a wave flume. The module responses of floating structures in various configurations are measured and analyzed in different wave periods and wave heights. In general, the response in longitudinal direction of multi-modular floating structure can be significantly improved by the increasing number of modules, while the effects of increasing modules on the heave and pitch responses are negligible. Based on the rigid module flexible connector (RMFC) model, validated by the experimental data, the connector loads of the experimental prototypes are assessed. The results indicate that longitudinal hinge loads increase doubly as modular number is added up to four, and afterwards increases very slow for further additional modules. The maximum longitudinal load usually occurs on the interior connectors, not on the connectors near the bow and stern. The level of vertical shear load mainly depends on the wave period rather than the number of modules in the floating platform. More detailed remarks are listed in conclusions. Highlights: This experiment aims to study the character transition of floating system as the structural layout gradually evolves. The response in longitudinal direction could be significantly improved by increasing the number of modules. The longitudinal hinge loads increase doubly as modular number is added up to four. The maximum longitudinal load occurs on the interior connectors, not on the connectors near the bow and stern. The level of vertical shear load mainly depends on the wave period rather than the quantity of modules.